Está en la página 1de 2

FACULTY OF APPLIED SCIENCES AND TECHNOLOGY

UNIVERSITI TUN HUSSEIN ONN MALAYSIA

BWM12303 TUTORIAL 3

Second order ordinary differential equations with constant coefficients

Homogenous equations
1. Find the general solution of each differential equation below.
d2 y dy d2 y dy
(a) 4 2 − 12 + 5 y = 0 (b) 2
−4 = −13 y
dx dx dx dx
d2 y
(c) + 9y = 0 (d) y ′′ − 10 y ′ + 25 y = 0
dx 2
Answer:
5 1
x x
(a) y = Ae 2 + Be 2 (b) y = e2 x ( A sin 3 x + B cos 3 x) (c) y = A sin 3 x + B cos 3 x (d) y = ( A + Bx ) e5 x

2. Solve the initial-value problem below.


(a) y ′′ − 4 y ′ + 29 y = 0, y (0) = 0, y ′(0) = 5
(b) 2 y ′′ + 8 y ′ + 8 y = 0, y (0) = 1, y ′(0) = 1
(c) y ′′ − 2 y ′ − 8 y = 0, y ( 0 ) = 2, y ′ ( 0 ) = 2
Answer:
(a) y = e2 x sin 5 x (b) y = (1 + 3 x ) e−2 x (c) y = e4 x + e−2 x

3. Solve the boundary-value problem below.


(a) y ′′ + 2 y ′ = 0, y (0) = 1, y (1) = e −2
(b) y ′′ + 4 y ′ + 13 y = 0, y (0) = 2, y ( π2 ) = 1
Answer:
(a) y = e−2 x (b) y = e−2 x ( 2 cos 3 x − eπ sin 3 x )

Nonhomogenous equations
Undetermined coefficients
1. Find the general solution of each differential equation below.
d2 y dy
(a) 2
− 3 = 4x2 − 2 y
dx dx
(b) 3 y − 6 y ′ − 9 y = 3e3 x
′′
(c) y ′′ + 2 y ′ + 5 y = 6sin x + 7 cos x
d 2 y dy
(d) + − 6 y = 18e3 x − 6 x − 11
dx 2 dx
Answer:
1 3x
(a) y = Ae 2 x + Be x + 2 x 2 + 6 x + 7 (b) y = Ae3 x + Be− x + xe
4
4 19
(c) y = e− x ( A cos 2 x + B sin 2 x) + cos x + sin x (d) y = Ae 2 x + Be−3 x + 3e3 x + x + 2
5 10

Prepared by Syahirbanun Isa


2. Solve the initial-value problems below.
(a) y ′′ − y = 3 x3 + x 2 − 1, y (0) = 1, y ′(0) = 2
(b) 2 y ′′ − y ′ − 3 y = 3 xe2 x , y (0) = 1, y ′(0) = 0
(c) y ′′ + 2 y ′ + 5 y = 4e−2 x − 1, y (0) = 1, y ′(0) = 0
(d) y ′′ + 5 y ′ − 6 y = 10e2 x , y (0) = 1, y ′(0) = 0

Answer:
3
14 2 x 8 − x 1
(a) y = 11e x − 9e − x − 3 x3 − x 2 − 18 x − 1 (b) y = e + e + ( −7 + 3 x ) e2 x
5 15 3
2  4 1 4 9 5
(c) y = e− x  cos 2 x + sin 2 x  + e −2 x − (d) y = − e x + e−6 x + e2 x
5  5 5 7 28 4

3. Solve the boundary-value problem below.


y ′′ + y = x 2 + 1, y (0) = 5, y (1) = 0
Answer:
y = 6 cos x − 6 cot(1) sin x + x 2 − 1

Variation of parameters

1. Find the general solution of each differential equation below.


d2y
(a) + y = cot x [Hint: ∫ csc x dx = ln csc x − cot x + C ]
dx 2
(b) y ′′ + 2 y ′ + y = e− x ln x

(c) y ′′ − 3 y ′ + 2 y = e 2 x cos x
Answer:
(a) y = A sin x + B cos x + sin x (ln | csc x − cot x |)
1
(b) y = ( A + Bx ) e − x + x 2 ( 2 ln x − 3) e− x
4
1
(c) y = Ae 2 x + Be x + + e 2 x ( sin x − cos x )
2

Prepared by Syahirbanun Isa